Information and communication technologies in primary healthcare facilities in Egypt - Farahat, Taghreed M. (Prim Health Care Res Dev, 2017)
BACKGROUND: The health sector has always relied on technologies. According to World Health Organization, they form the backbone of the services to prevent, diagnose, and treat illness and disease. It is increasingly viewed as the most promising tool for improving the overall quality, safety and efficiency of the health delivery system. AIM OF THE STUDY: This was to assess the current situation of information and communication technologies (ICTs) in primary healthcare in the terms of describing and classifying the existing work, identify gaps and exploring the personal experiences and the challenges of ICTs application in the primary healthcare. SUBJECTS AND METHODS: A mixed research method in the form of sequential explanatory design was applied. In the quantitative phase a cross-sectional study was conducted among 172 family physicians using a predesigned questionnaire. Followed by qualitative data collection among 35 participants through focused group discussions. RESULTS: Nearly half of the physicians have ICTs in their work and they were trained on it. None of them developed a community-based research using ICTs technology. Training on ICTs showed a statistically significant difference regarding the availability and the type of ICTs present in the workplace (P<0.05). Focused group discussion revealed that the majority of the participants believe that there is poor commitment of policymaker toward ICTs utilization in the primary care. Nearly 97% thinks that there is insufficient budget allocated for ICTs utilization in the workplace. Almost 88% of the participants demanded more incentives for ICTs users than non-user at the workplace. CONCLUSIONS: ICTs resources are underutilized by health information professionals. Lack of funds, risk of instability of the electric supply and lack of incentives for ICTs users were the most common barriers to ICTs implementation thus a steady steps toward budget allocation and continuous training is needed.